Microstructure characterization and mechanism of acoustoplastic effect in friction stir welding assisted by ultrasonic vibrations on the bottom surface of workpieces. (June 2019) - Liu, Huijie; Hu, Yanying; Du, Shuaishuai; Zhao, Huihui
Graphical abstract: Abstract: Considering the acoustoplastic effect, an application of ultrasonic vibrations to Friction Stir Welding (FSW) evokes more and more interests in recent years. The material in the lower region of one FSW joint is the most in need of acoustic energy to improve its flow ability due to a relatively low peak temperature over there. However, the backing plate in Conventional Friction Stir Welding (CFSW) prevents the ultrasonic vibrations from being directly transmitted from the workpiece bottom surface. One aim of this paper was to propose an innovative welding technique, i.e. friction stir welding assisted by ultrasonic vibrations on the bottom surface of workpieces (UVBS-FSW). Precipitates evolution in different zones of the joint was analyzed in detail. High-density helical dislocations and prismatic dislocation loops were detected, indicating a significant increase of vacancy density. With the vacancy density increasing, the climb of jogs and edge dislocations were both enhanced and thus the intrinsic resistance of deformation can be significantly reduced. The enhanced mobility of dislocations as a result of high-density vacancy due to the application of ultrasonic vibrations is the physical nature of the acoustoplastic effect.